2014
DOI: 10.3390/nu6041554
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administrated Ascorbic Acid Suppresses Neuronal Damage and Modifies Expression of SVCT2 and GLUT1 in the Brain of Diabetic Rats with Cerebral Ischemia-Reperfusion

Abstract: Diabetes mellitus is known to exacerbate cerebral ischemic injury. In the present study, we investigated antiapoptotic and anti-inflammatory effects of oral supplementation of ascorbic acid (AA) on cerebral injury caused by middle cerebral artery occlusion and reperfusion (MCAO/Re) in rats with streptozotocin-induced diabetes. We also evaluated the effects of AA on expression of sodium-dependent vitamin C transporter 2 (SVCT2) and glucose transporter 1 (GLUT1) after MCAO/Re in the brain. The diabetic state mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Hence, it appears that AA may suppress oxidative stress and the accumulation of free radicals and thereby inhibit the side effects of r-tPA. Recently, Iwata et al (2014) [15] found that chronic AA supplementation inhibits apoptotic and pro-inflammatory changes and attenuates brain injury and neurological deficits in STZ-induced diabetic rats. Our results showed that the levels of MMP-9 and brain oedema increased after the induction of permanent MCAO and also after therapy with r-tPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it appears that AA may suppress oxidative stress and the accumulation of free radicals and thereby inhibit the side effects of r-tPA. Recently, Iwata et al (2014) [15] found that chronic AA supplementation inhibits apoptotic and pro-inflammatory changes and attenuates brain injury and neurological deficits in STZ-induced diabetic rats. Our results showed that the levels of MMP-9 and brain oedema increased after the induction of permanent MCAO and also after therapy with r-tPA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that antioxidant treatment with AA significantly reduces lipid peroxidation and increases superoxide dismutase and catalase activities after seizures induced by pilocarpine [14]. Moreover, AA is an essential antioxidant for scavenging free radicals in the brain and may protect endothelial function against the exacerbated ischaemic oxidative injury in diabetes [15]. Furthermore, oxidative stress is an early trigger for the up-regulation of MMP-9 which in turn contributes to BBB damage after cerebral ischaemia reperfusion [16,17].…”
mentioning
confidence: 99%
“…AA mainly relies on Na + -dependent transporter, while DHA was mediated by glucose transporter (GLTU) [35,36]. Besides, DHA has been reported to be reduced to AA at first inside the cell, and it is AA that played key anti-oxidant roles [37,38]. It was indicated in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, hyperglycemia per se causes decrease in reperfusion blood flow by facilitating vasoconstriction (Martini and Kent, 2007). Further, various research groups have used the endovascular MCAO model to assess the benefit of different therapeutic strategies proposed to treat the enhanced neurodegeneration associated with stroke among diabetics (Briyal et al, 2012; Cui et al, 2012; Darsalia et al, 2014; Iwata et al, 2014; Simard et al, 2009; Song et al, 2014; Yan et al, 2013). The endovascular MCAO model has been used to study diabetic aggravation of ischemic brain damage in db/db diabetic mice (Chen et al, 2012; Chen et al, 2011) and SHR rats (Slivka, 1991).…”
Section: Animal Models Of Cerebral Ischemia Used To Study Effects mentioning
confidence: 99%